Fabrication, applications and challenges of natural biomaterials in tissue engineering. (September 2020) - Ullah, Saleem; Chen, Xin
Abstract: Natural biomaterials are extensively used in tissue engineering due to their microstructure interconnectivity and inherent bioactivity which mimics of natural extracellular matrix (ECM), supporting cell infiltration, adhesion, differentiation, transportation of oxygen and nutrient, finally restoring the structure and function of defective tissues or organs. Microstructure, mechanical properties, biostability and cellular activity of natural biomaterials are controlled via blending of natural or natural with synthetic biopolymers and physical/chemical crosslinking treatments to allow the required mechanical strength, degradation rate and ECM mimic microenvironment for supporting of cellular activity. In addition, natural biomaterials also performed a key role in delivery of cells, bioactive molecules, growth factors and drugs. In this review, we will explore the fabrication, challenges and applications of natural biomaterials for various tissues engineering issues, including polymer selection, fabrication techniques, microstructure manipulation, physical/chemical crosslinking, mechanical properties, biostability as well as their role in delivery of cells, bioactive molecules, growth factors and drugs.